Identification and Evaluation of Reference Genes for Quantitative PCR Normalization in Alligator Weed Flea Beetle (Coleoptera: Chrysomelidae). Issue 5 (30th September 2021) - Guo, Yan-Qiong; Yang, Yongchang; Chai, Yanping; Gao, Ling-Ling; Ma, Ruiyan
Abstract: Stably expressed reference genes are critical internal standards for the quantification of gene transcription levels using quantitative real-time PCR. Housekeeping genes are commonly used as reference genes but their expressions were variable depending on experimental conditions in many insect species studied. Here we report the identification and evaluation of 10 housekeeping genes in alligator weed flea beetle, Agasicles hygrophila Selman & Vogt (Coleoptera: Chrysomelidae), a biocontrol agent of alligator weed. The 10 housekeeping genes are: beta-actin ( Actin ), ribosomal protein L13A ( PRL13a ), succinate dehydrogenase complex subunit A ( SDHA ), ribosomal protein S20 ( RPS20 ), ribosomal protein S13 ( RPS13 ), glyceraldehyde phosphate dehydrogenase ( GAPDH ), TATA-box-binding protein ( TBP ), ribosomal protein L32 ( RPL32 ), tubulin alpha-1 chain ( TUBULIN ), and elongation factor-1 alpha ( ELF ). Five programs, geNorm, NormFinder, BestKeeper, ΔCt method, and RefFinder, were used to evaluate the expression stability of the 10 genes among various A. hygrophila body parts and with different nutrient types (starvation, diet types). The expression stability analysis showed that RPS32 and RPL13a were reliable reference genes for the study of gene transcription in different body parts; Actin and RPL13a were optimal reference genes for different nutrient types. The selections of reference genes were validated using a CarE gene (GeneBank No: KX353552). The results of this study provide useful bases for studies of gene expression in various aspects relating to A. hygrophila .